2024
DOI: 10.3390/polym16060739
|View full text |Cite
|
Sign up to set email alerts
|

Specific FRET Probes Sensitive to Chitosan-Based Polymeric Micelles Formation, Drug-Loading, and Fine Structural Features

Igor D. Zlotnikov,
Ivan V. Savchenko,
Elena V. Kudryashova

Abstract: Förster resonance energy transfer (FRET) probes are a promising tool for studying numerous biochemical processes. In this paper, we show the application of the FRET phenomenon to observe the micelle formation from surfactants, micelles self-assembling from chitosan grafted with fatty acid (oleic—OA, or lipoic—LA), cross-linking of SH groups in the micelle’s core, and inclusion and release of the model drug cargo from the micelles. Using the carbodiimide approach, amphiphilic chitosan-based polymers with (1) SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…FRET is observed in aqueous solution for between MUmb-derivative and R6G, but the FRET effect is rather weak, since the donor and acceptor molecules separated from each other in the volume of the solution [7]. A different situation is observed for reverse micellar system, where the enzyme and the reaction components are located in a limited volume of the aqueous phase of the inner cavity of the micelles.…”
Section: Objects Of Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…FRET is observed in aqueous solution for between MUmb-derivative and R6G, but the FRET effect is rather weak, since the donor and acceptor molecules separated from each other in the volume of the solution [7]. A different situation is observed for reverse micellar system, where the enzyme and the reaction components are located in a limited volume of the aqueous phase of the inner cavity of the micelles.…”
Section: Objects Of Researchmentioning
confidence: 97%
“…Previously, we demonstrated that the FRET effect is not as pronounced in aqueous solutions, whereas in micellar systems, this effect is significantly stronger [7]. FRET probes are further applied to study the enzymatic activity in the membrane-like systems such as reverse micelles.…”
Section: Theoretical Comparison Of Expected Fret Effects In a Buffer ...mentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Reducing agents such as GSH, dithiothreitol (DTT), and β-mercaptoethanol can react with disulfide bonds, converting them into thiol groups. 29 , 30 The thiol group on cysteine in GSH serves as its active center. Through redox reactions and nucleophilic substitution reactions, disulfide bonds are broken down into thiol groups by GSH, leading to the rapid degradation of the carrier and facilitating drug release for therapeutic effects.…”
Section: Basis Of Action Of Disulfide Bondmentioning
confidence: 99%